M. Kogălniceanu în corespondenţă (V) Scrisori din timpul studiilor la Lunéville şi Berlin (1834–1838) - Andrei Nestorescu (Revista de Istorie și Teorie Literară)
The author publishes some letters belonging to Mihail Kogălaniceanu, letters he addresses to his father and sisters, but especially to his father. The letters he writes to his sister are all in French. He shares with them his experience as a student in Lunnéville and Berlin, between 1834 and 1838, and he thanks them for the concern and the care they show for his well-being. Besides the letters, Andrei Nestorescu publishes as well a list containing the names Kogălniceanu refers to and an explanatory dictionary for all the words used by Kogălniceanu (regionalisms and archaisms). Mihai Kogălniceanu is rediscovered as a writer in his vast and picturesque correspondence. The vocabulary in these numerous letters is archaic but disposes of a peculiar fragrance. Encompassing a period of over fifty-seven years, this correspondence brings testimony about the western realities of those times, contrasted to the Moldavian ones. In this way, it can be taken as a document about the habits and ideals of the 1848 generation.